2003
DOI: 10.1111/j.1945-5100.2003.tb00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Ca and Al between forsterite and silicate melt in dynamic systems with implications for the origin of Ca, Al‐rich forsterites in primitive meteorites

Abstract: Abstract-We report the results of dynamic crystallization experiments that were specifically designed to study the dependence of Ca and Al partitioning between forsterite and melt in rapidly cooling Caand Al-rich melts. The partitioning of Ca between olivine and silicate melt is found to be independent of the cooling rate within the range of 1.5 to 1000°C/hr and at CaO contents of up to 25 wt%. Within analytical uncertainty, our data plot on the equilibrium partitioning curve obtained by Libourel (1999). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 27 publications
9
53
2
Order By: Relevance
“…2C, E and I). Similar to the observations by Pack and Palme (2003) and Pack et al (2004), concentrations of Ca and Al either decrease from core to rim ( Fig. 1A and B) or are constant throughout the grains (Fig.…”
Section: Mineral Chemistrysupporting
confidence: 82%
See 2 more Smart Citations
“…2C, E and I). Similar to the observations by Pack and Palme (2003) and Pack et al (2004), concentrations of Ca and Al either decrease from core to rim ( Fig. 1A and B) or are constant throughout the grains (Fig.…”
Section: Mineral Chemistrysupporting
confidence: 82%
“…10C and E). Pack and Palme (2003) and Pack et al (2004) have shown that high CL intensity is caused by low Fe and high concentrations of Al and especially Ti. Olivine with low concentra- tions of Fe and low concentrations of Al and Ti does not show CL emission.…”
Section: Sampling and Petrographymentioning
confidence: 97%
See 1 more Smart Citation
“…Both Al and Ti can be sector-zoned in experimental samples, in contrast to Ca, though the effect is minor (Pack and Palme, 2003); the volume-averaging nature of LA-ICP-MS means no such effect was evident in the present study. It is notable that Ca is found only on the Msites of olivine, whereas Al and Ti both partition partially onto the Si site (Hermann et al, 2005;Wan et al, 2008), but the petrological significance of sector zoning remains to be established.…”
Section: Accepted Manuscriptcontrasting
confidence: 80%
“…Although without the classic hourglass shape (e.g., Strong 1969), this feature may be a kind of sector zoning. As shown experimentally by Pack and Palme (2003), olivine can develop classic hourglass sector zoning. Another P-poor region that may relate to sector zoning is observed in a Hawaiian microphenocryst ( Fig.…”
Section: A[e] 5a[a])mentioning
confidence: 82%